The Effect of the Effectiveness of the use of Financial Information Systems, Task Suitability, and Computer User Expertise on Employee Performance - Sahusilawane, Wildoms (PT FORMOSA CENDEKIA GLOBAL, 2024)
This study examines the effect of the effectiveness of financial information systems, task suitability, and computer user expertise on the performance of employees of Universitas Terbuka. The sample of this study was 51 respondents selected by purposive sampling. Primary data were obtained from questionnaires and interviews and then analysed with multiple correlation and regression tools using the SPSS application. The results of the F-test analysis show that the three variables have a positive and significant effect on employee performance. The t-test results also show that the variable effectiveness of using financial information systems has a positive and significant influence on employee performance, while the variable of task suitability and expertise of computer users does not have a significant effect.